THE USE OF MINIMAL PAIR TECHNIQUE IN TEACHING PRONUNCIATION AT THE SECOND YEAR STUDENTS OF SMAN 4 BANTIMURUNG - Indah Fadhilah Rahman (Universitas Islam Negeri Alauddin Makassar, 2018)
This objectives of this research were to find out (1) Use of minimal pair technique in teaching pronunciation at the second year students of SMAN 4 Bantimurung. (2) Whether the minimal pair technique effective in teaching pronunciation or not at the second year students of SMAN 4 Bantimurung. This researcher applied quasi-experimental design with non-equivalent control group design. The sample was taken by using purposive sampling that devided into two groups were 25 students as experimental class and 25 students as control class. The result of the data indicated that there was a significance difference between students’ post-test in the experimental class and the control class. The mean score of post-test (2.96) in the experimental class was greater than the mean score of post-test (2.2) in the control class and the standard deviation of the post-test (0.83) in experimental class was greater than the standard deviation of the post–test (0.4) in control class and the value of t-test (5.84) was higher than t-Table (2.021). Based on the result of this study implies that use of minimal pair technique was effective to improve the students’ pronunciation ability at the second year students of SMA Negeri 4 Bantimurung. Besides, the significant improvement can be seen from the students’ response to researcher’s performance. They seem more active during teaching learning activity. Therefore, the researchers suggests that the English teacher should implement minimal pair technique in teaching pronunciation in order to improve students’ pronunciation ability.